Pengaruh Pemanfaatan Teknologi Augmented Reality terhadap Tingkat Ketertarikan Belajar Siswa dalam Penyampaian Materi Pembelajaran - Uci Purnama Sari; Dina Mayadiana Suwarma; Desty Endrawati Subroto; Roswati Roswati; Jenuri Jenuri; I Putu Agus Dharma Hita (Departement of Mathematics Education, 2024)
This research aims to explore the influence of Augmented Reality (AR) technology utilization on students' level of learning interest in delivering learning materials. A literature review method was employed to gather and analyze relevant sources of data regarding the research topic. The research findings indicate that the use of AR technology in learning contributes positively to students' level of learning interest. AR provides an interactive, captivating learning experience that captures students' attention by presenting learning materials in visual and sensory formats. Moreover, AR also enhances students' learning motivation through enjoyable and satisfying learning experiences. These findings suggest that educators should actively integrate AR technology into learning to improve the quality and effectiveness of the teaching-learning process.